DEGRADASI KATALITIK ZAT WARNA METIL JINGGA MENGGUNAKAN KATALIS OKSIDA MANGAN MANGANOSITE - Subkhan, Mokhamad; Awaluddin, Amir; -, Presetya -; Siregar, Siti Saidah; Anggraini, Riska (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2018)
Preparation of manganese oxide by sol-gel method and its application as a catalyst for methyl orange (MO) degradation was carried out using hydrogen peroxide as an oxidant.The characterization of manganese oxide was conducted using X-Ray Diffraction and Scanning Electron Microscope. The effect of initial concentration of MO was examined. Degradation efficiency was decrease with increasing the concentration of MO. The degradation kinetics ofMO followed the second-order reaction kinetics.